Distributed event-triggered control strategies for multi-agent systems - Dimarogonas, D.V.; Frazzoli, E. (2009 47th Annual Allerton Conference on Communication, Control, and Computing, 2009)
Event-driven strategies for distributed multi-agent systems are motivated by the future use of embedded microprocessors with limited resources that will gather information and actuate the individual agent controller updates. The event-driven control actuation updates considered in this paper are distributed, in the sense that agents require knowledge only of the states of their neighbors for the controller implementation. The proposed distributed strategy is compared with an earlier approach.